1997
DOI: 10.1103/physrevlett.79.2759
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Irreversible Entropy Production in Driven Systems: An Elementary Chaotic Map Approach

Abstract: A multibaker map is generalized in order to mimic the thermostating algorithm of transport models. Elementary calculations yield the irreversible entropy production caused by coarse graining of the phase-space density. For different systems, either in steady states (periodic or flux boundaries) or subjected to absorbing boundaries, the specific irreversible entropy production is shown to be u 2 ͞D, where u denotes the local streaming velocity (current per density) and D is the diffusion coefficient. [S0031-900… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 28 publications
(43 reference statements)
0
76
0
Order By: Relevance
“…Significant progress has been made recently in the theory for entropy production in nonequilibrium, Hamiltonian systems, using ideas from dynamical systems theory. Gaspard [1], Tél, Vollmer, and Breymann [2][3][4][5], Gilbert and Dorfman [6], as well as Tasaki and Gaspard [7,8], have described coarse graining procedures applied to the Gibbs entropy, defined in the phase space of systems maintained in nonequilibrium steady states. These procedures lead to results in accord with the predictions of the thermodynamics of irreversible processes.…”
Section: (Received 7 March 2000)mentioning
confidence: 99%
“…Significant progress has been made recently in the theory for entropy production in nonequilibrium, Hamiltonian systems, using ideas from dynamical systems theory. Gaspard [1], Tél, Vollmer, and Breymann [2][3][4][5], Gilbert and Dorfman [6], as well as Tasaki and Gaspard [7,8], have described coarse graining procedures applied to the Gibbs entropy, defined in the phase space of systems maintained in nonequilibrium steady states. These procedures lead to results in accord with the predictions of the thermodynamics of irreversible processes.…”
Section: (Received 7 March 2000)mentioning
confidence: 99%
“…A closely related, independent approach to the problem of entropy production in non-equilibrium steady states is provided by Tél, Vollmer, and Breymann (TVB) in a series of papers [1,19,2,20], also devoted to diffusion in multibaker models. These authors considered the entropy production in measure preserving maps as well as in dissipative maps that do not preserve the Lebesgue measure and model systems with Gaussian thermostats.…”
Section: Introductionmentioning
confidence: 99%
“…A generalization of the methods of Gaspard [7,8] and TVB [1,19,2,20] was proposed by the present authors in a recent paper [9], where it was shown that a coarse-grained form of the Gibbs entropy, which can be expressed in terms of the measures and volumes of the coarse graining sets partitioning the phase, leads to an entropy production formula similar to Gaspard's and applicable to more general volume-preserving as well as dissipative models, such as those considered by TVB, as well as multi-baker maps with energy flow considered by Tasaki and Gaspard [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the following we revisit this argument in the light of recent developments [13,17] dealing with steady states instead of empty asymptotic states. We work out the irreversible entropy production for an isothermal multibaker map with reversible microscopic dynamics subjected to absorbing boundary conditions.…”
Section: Entropy Production Based On Conditional Invariant Measurmentioning
confidence: 99%
“…Multibaker maps model particle transport in spatially extended systems by a chain of mutually interrelated baker maps [13,14,17,18,19,20,21,22,23,24]. They consist of N identical cells of width a and height 1 (the phase-space) in the (x, p) plane.…”
Section: The Isothermal Multibaker Mapmentioning
confidence: 99%